2014
DOI: 10.1007/s10803-014-2126-6
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy Among Children and Adolescents with Autism Spectrum Disorders: A Population-Based Study

Abstract: The present population-based study examines associations between epilepsy and autism spectrum disorders (ASD). The cohort includes register data of 4,705 children born between 1987 and 2005 and diagnosed as cases of childhood autism, Asperger's syndrome or pervasive developmental disorders--not otherwise specified. Each case was matched to four controls by gender, date of birth, place of birth, and residence in Finland. Epilepsy was associated with ASD regardless of the subgroup after adjusting for covariates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
56
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 45 publications
8
56
2
Order By: Relevance
“…Other reports estimate that approximately 20–25% children with ASD have epilepsy [21]. A recent population-based study found 44% of children with ASD received a subsequent diagnosis of epilepsy, and 54% of children with epilepsy received a subsequent diagnosis of ASD [22]. Age of onset for epilepsy in ASD is bimodally distributed, with a peak in early childhood (age 2–5 years) and a larger peak in adolescence [23].…”
Section: Case Definitions Of Asdmentioning
confidence: 99%
“…Other reports estimate that approximately 20–25% children with ASD have epilepsy [21]. A recent population-based study found 44% of children with ASD received a subsequent diagnosis of epilepsy, and 54% of children with epilepsy received a subsequent diagnosis of ASD [22]. Age of onset for epilepsy in ASD is bimodally distributed, with a peak in early childhood (age 2–5 years) and a larger peak in adolescence [23].…”
Section: Case Definitions Of Asdmentioning
confidence: 99%
“…Caring for someone with ASD presents significant challenges: individuals with ASD may become distressed when routines are disturbed (DeGrace 2004), and have difficulties expressing their needs (Peppe et al 2007). Medical comorbidities are also common, including a higher prevalence of epilepsy and sleep disorders when compared to the general population (Bauman 2010; Jokiranta et al 2014). Furthermore, with the majority of adults with ASD remaining dependent on their families (Howlin et al 2013, 2004), the role of a parent as a carer pervades throughout life.…”
Section: Introductionmentioning
confidence: 99%
“…Other data suggest an increased occurrence of epilepsy in female patients with ASD compared with male patients with ASD. 6,9,13 This may be especially so in female patients with comorbid intellectual disability. 9 In the Amiet et al 13 meta-analysis, the male:female ratio of autism comorbidity with epilepsy was 2:1, whereas the male: female ratio of autism without epilepsy was 3.5:1.…”
mentioning
confidence: 99%
“…22 The occurrence of the specific epilepsy diagnosis varied in different studies of individuals with ASD and comorbid epilepsy, primarily generalized between 14% and 24%, partial onset between 30% and 44%, and the dominating group had unspecified epilepsy (G40.9). 6,9,23 We have therefore not analyzed the different epilepsy codes separately.…”
mentioning
confidence: 99%